Quantitative proteomics analysis reveals unique but overlapping protein signatures in HIV infections - Maha Al-Mozaini; Alhusain Alzahrani; Ibtihaj Alsharif; Zakia Shinwari; Magid Halim; Abdullah Alhokail; Abdulrahman Alrajhi; Ayodele Alaiya (Elsevier, 2021)
Background: Human immunodeficiency virus-1 (HIV-1) exploits human host factors to complete its life cycle. Hence, discovery of HIV-regulated host proteins markers would better our understanding of the virus life-cycle and its contribution to pathogenesis and discovery of objective diagnostic and prognostic molecules. Methods: We conducted holistic total proteomics analysis of three closely related study populations including patients with HIV type-1 (HIV-1) and HIV type-2 (HIV-2) as well as HIV-1 elite controllers (HIV-1-EC). Peripheral blood plasma (PBP) samples were subjected to label-free quantitative liquid-chromatography tandem mass-spectrometry (LC-MS/MS). Results: Over 314 unique PBP protein species were identified of which 100 (approx. 32%) were significantly differentially expressed (≥2 to ∞ - fold-change; p < 0.05) between the three sample cohorts. Of the 100 proteins, 91 were significantly changed between pairs of HIV-1 versus HIV-1-EC, while 83 of the 100 proteins differed significantly between HIV-2 and HIV-1-EC. Interestingly, 76 proteins (87.5%) overlap between the two data sets indicating that majority of these proteins share similar expression changes between HIV-1 and HIV-2 sample groups. Two of the identified proteins, XRCC5 and PSME1, were implicated in the early phase of the pathway network for HIV life cycle, while others were involved in infectious disease and disease of signal transduction. Among them were MAP2K1, RPL23A, RPS3, CALR, PRDX1, SOD2, LMNB1, PHB, and FGB. Despite the high degree of similarity in protein profiles of HIV-1 and HIV-2, six proteins differed significantly including ETFB, PHB2, S100A9, LMO2, PPP3R1 and Vif, a fragment of virion infectivity factor of HIV-1. Additionally, 15 proteins were uniquely expressed, and one of them (LSP1) is present only in HIV-1-EC but absent in HIV1 and HIV-2 and vice versa for the rest 14 proteins. Conclusions: Altogether, we have identified HIV-specific/related protein expression changes that might potentially be capable of early diagnosis and prognosis of HIV diseases and other related infectious diseases.